Is the Santa Inês sheep a typical non-seasonal breeder in the Brazilian Southeast? - Balaro, Mario Felipe Alvarez; da Fonseca, Jeferson Ferreira; Oba, Eunice; da Cruz Cardoso, Elyzabeth; Brandão, Felipe Zandonadi (Springer Nature, 2014)
This study aimed to characterize the annual reproductive cycle of Santa Inês sheep in the Fluminense lowland region (latitude 22° 27′ 45″ south, Rio de Janeiro, Brazil) between September 2011 and August 2012. Ten ewes were maintained in a semi-intensive system under natural photoperiods with access to pasture and shelter. Blood samples were collected every 2 weeks to determine plasma progesterone concentrations. The body condition score (BCS) was determined each month. There was no seasonal variation in the plasma progesterone concentration from the months of September to January, April, and May to August. In the months of February and April, the plasma hormone levels were higher than August to November. Seventy percent (7/10) of the sheep studied had short seasonal anestrus. The periods of anestrus were concentrated between the months of September and December (spring season) in 85.7 % (6/7) of the cases evaluated. In these cases, 57.1 % (4/7) also had short periods of reproductive inactivity during other months of the year. The progesterone values obtained in the spring corroborate the higher reproductive anestrus observed in this season. Higher plasma progesterone values were found in summer and autumn with reduction in the winter to lower values in the spring. No changes in the BCS during the study period were observed. Under the studied conditions, the Santa Inês sheep showed a low degree of reproductive seasonality. However, some individual ewes had seasonal anestrus during the spring. Further studies that include management techniques are needed to improve reproductive efficiency without hormone therapy in this breed under tropical conditions.
Keywords: Cyclicity; Progesterone; Reproductive seasonality; Tropical hair sheep